2006
DOI: 10.1002/bdd.500
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro metabolism of ciclesonide in human lung and liver precision‐cut tissue slices

Abstract: Ciclesonide is a new-generation inhaled corticosteroid developed to treat the inflammation associated with persistent asthma. In order to identify the properties of ciclesonide responsible for anti-inflammatory activity, ciclesonide metabolism was investigated in human lung and liver precision-cut tissue slices. Three human lung and three human liver tissue slices were incubated with 25 microM [14C]-ciclesonide for 2, 6 and 24 h. Cellular viability was assessed using adenosine 5'-triphosphate content and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 32 publications
4
60
1
Order By: Relevance
“…We have shown earlier in this system that only the intact BUD (and not BUD esters) is released from trachea into incubation medium (MillerLarsson et al, 1998). Similarly, only CIC and CIC-AM, but not CIC-AM esters, were detected in medium after incubation with human lung slices (Nave et al, 2006b).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We have shown earlier in this system that only the intact BUD (and not BUD esters) is released from trachea into incubation medium (MillerLarsson et al, 1998). Similarly, only CIC and CIC-AM, but not CIC-AM esters, were detected in medium after incubation with human lung slices (Nave et al, 2006b).…”
Section: Resultsmentioning
confidence: 85%
“…CIC is inactive, but it is hydrolyzed to an active metabolite (CIC-AM) that was reported to form fatty acid esters in airway tissue. CIC-AM esters have been detected in vitro in human alveolar and nasal epithelial cells (Nave et al, 2005b(Nave et al, , 2006c and in rat and human lung slices (Nave et al, 2004(Nave et al, , 2006a. They were also detected after inhalation of CIC in rat and human lungs (Nave et al, 2005a;Watz et al, 2006).…”
mentioning
confidence: 99%
“…[8,21,22] Ciclesonide fatty acid conjugates are five-fold more lipophilic than budesonide fatty acid conjugates. [7] Increased lipophilicity and the ability to form fatty acid conjugates may increase ciclesonide retention in the lung [7,8] and, thereby, may contribute to the clinical efficacy of once-daily ciclesonide observed in this study. In addition, the high pulmonary deposition of ciclesonide and the high affinity of the active metabolite for the glucocorticoid receptor potentially contribute to the improvements in lung function and asthma symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Subsequently, des-CIC undergoes reversible esterification to form fatty acid conjugates in the lung that serve as a depot for the slow release of the active drug. [8] Finally, des-CIC is converted into a series of inactive metabolites that are eliminated from the body. [9] Several clinical studies have reported the efficacy and safety profiles of ciclesonide in patients with persistent asthma over a range of doses (80-640 µg).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies in human tissue and in vivo studies in rats have reported that des-CIC forms reversible conjugates with fatty acids, which are pharmacologically inactive and do not bind to the glucocorticoid receptor [7,[13][14][15]. The findings regarding the metabolism of CIC derived from in vitro and animal studies have yet to be confirmed by in vivo studies in human subjects.…”
mentioning
confidence: 99%